Nonlinear Analysis of The Kinetics and Equilibrium for Adsorptive Removal of Paranitrophenol by Powdered Activated Carbon - N’diaye, Abdoulaye Demba (Universitas Pendidikan Indonesia (UPI), 2023)
Paranitrophenol (PNP) is one of the toxic chemicals, non-degradable, and bioaccumulative. In the present work, the nonlinear analysis method was used to assess the kinetics and equilibrium for PNP adsorption on commercially available Powdered Activated Carbon (PAC) from an aqueous solution. The adsorption kinetic data were analyzed using the Pseudo First Order (PFO), Pseudo Second Order (PSO), and Elovich models. The experimental data were fitted using two-parameter isotherms model (Langmuir, Freundlich and Temkin) and three parameters isotherms model (Sips, Redlich – Peterson and Toth). For the kinetic study, the adsorption process fitted the PSO model. Among two-parameter models, the Freundlich is better described for PNP adsorption on PAC. From three-parameter isotherms, the Sips model was found to be the best representative for PNP adsorption on the PAC. The results of the present study showed the efficiency of using PAC as an adsorbent for the removal of PNP from an aqueous solution.